Gender Negotiation in Pop Music: A Critical Discourse Analysis of Empowerment in “Power” by Little Mix ft. Stormzy - Hendy Nabil Rais (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2025)
Pop music serves as a significant medium for gender representation, yet mainstream songs often reproduce patriarchal narratives that objectify women. This study examines how "Power" by Little Mix featuring Stormzy constructs female empowerment discourse within commercial pop culture. Employing Fairclough's three-dimensional critical discourse analysis, this qualitative research analyzes textual, discursive, and social practices. Data sources include official lyrics, the music video, behind-the-scenes materials, and a purposive sample of 50 most-liked TikTok videos using the song. Results reveal that "Power" negotiates gender meanings through: (1) appropriation of masculine metaphors ("machine," "engine") into female agency narratives, (2) strategic cross-gender collaboration that maintains female narrative control, (3) inclusive visual representation featuring mothers and drag queens, and (4) participatory digital remix culture that extends the song’s discourse. The study demonstrates how mainstream artists may disrupt patriarchal norms through symbolic strategies embedded within commercial systems. These findings contribute to understanding pop music as a site for gender renegotiation, particularly relevant for Indonesia where young audiences actively engage with global feminist messages. Future research should explore audience reception through digital ethnography and investigate how local music genres negotiate similar discursive tensions.